Mentoring in Writing Scientific Papers on the Theme of STEAM for Teachers of MA and MTs Alif Laam Miim Surabaya - Hadi Suwono; Ahmad Taufiq; Sri Rahmawati; Hendra Susanto; Arif Hidayat; Lya Rizka Herawati (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
This community service activity is based on the lack of understanding and ability of high school and junior high school teachers in compiling scientific articles and introducing much more deeply about learning methods using the STEAM approach. In addition, many teachers are still reluctant to publish research results on the grounds that they do not understand the guidelines for compiling scientific articles. This is the basis for the need to carry out this community service activity with the aim of helping high school and junior high school teachers in compiling scientific articles so that later teachers can publish articles that have been made in journals or mass media and are able to apply learning methods with STEAM. The community service activity was carried out in October 2022 at the State University of Malang. The method used is divided into two stages, namely delivering material and mentoring for teachers who want to compile scientific articles according to the reports they have. With this community service activity, it can provide a new knowledge concept for teachers so that they can compile scientific articles, especially from the results of research that has been carried out.